Long‐term outcomes of self‐expanding versus balloon‐expandable transcatheter aortic valves: Insights from the OBSERVANT study. Issue 6 (13th April 2021) - Costa, Giuliano; D'Errigo, Paola; Rosato, Stefano; Valvo, Roberto; Biancari, Fausto; Tamburino, Corrado; Cerza, Francesco; Cicala, Stefano Domenico; Seccareccia, Fulvia; Barbanti, Marco; ,
Abstract: Objectives: To compare clinical outcomes of balloon‐expandable (BE) and self‐expanding (SE) transcatheter aortic valves (TAVs) up to 5 years. Background: To date, no robust, comparative data of BE and SE TAVs at long‐term are available. Methods: We considered a total of 1, 440 patients enrolled in the multicenter OBSERVANT study and undergoing transfemoral transcatheter aortic valve implantation (TF‐TAVI) with either supra‐annular SE ( n  = 830, 57.6%) and intra‐annular BE ( n  = 610, 42.4%) valves. Clinical outcomes of the two groups were compared after adjustment using inverse probability of treatment weighting (IPTW) and confirmed by sensitivity analysis with propensity score matching. Results: Patients receiving SE valve showed a higher all‐cause mortality at 5 years (Kaplan–Meier estimates 52.3% vs. 47.7%; Hazard ratio [HR] 1.18, 95% confidence interval [CI] 1.01–1.38, p  = .04). Landmark analyses showed that there was a not statistically significant reversal of risk excess against the BE group starting from 3 years after TAVI (3–5 years HR 0.97, 95% CI 0.76–1.25, p  = .86). Post‐procedural, moderate/severe paravalvular regurgitation (PVR)(HR 1.46, 95% CI 1.14–1.87; p  < .01) and acute kidney injury (AKI)(HR 3.89, 95% CI 2.47–6.38; p  < .01) showed to be independent predictors of 5‐year all‐cause mortality in multivariable analysis. Conclusions: Considering the intrinsic limitations of the OBSERVANT study, we found that patients undergoing TF‐TAVI with a supra‐annular SE valve had a higher all‐cause mortality compared to those receiving an intra‐annular BE valve at 5 years. A late catch up phenomenon of patients receiving the BE valve was observed beyond 3 years. Post‐procedural moderate/severe PVR seems to play a crucial role in determining this finding. Comparative studies of new generation devices with longer follow‐up are needed to evaluate the benefit of each specific TAV type.